2020
DOI: 10.3389/fcimb.2020.587948
|View full text |Cite
|
Sign up to set email alerts
|

From Welfare to Warfare: The Arbitration of Host-Microbiota Interplay by the Type VI Secretion System

Abstract: The health of mammals depends on a complex interplay with their microbial ecosystems. Compartments exposed to external environments such as the mucosal surfaces of the gastrointestinal tract accommodate the gut microbiota, composed by a wide range of bacteria. The gut microbiome confers benefits to the host, including expansion of metabolic potential and the development of an immune system that can robustly protect from external and internal insults. The cooperation between gut microbiome and host is enabled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 144 publications
(163 reference statements)
0
20
0
Order By: Relevance
“…Genes encoding for the Type VI Secretion System (T6SS) are present in more than 25% of Proteobacteria (Bingle et al, 2008;Barret et al, 2013). The injection of a panel of T6SS effectors into competing bacteria promotes the fitness of T6SS-positive strains in polymicrobial environments, including the gut ecosystem (Coulthurst, 2019;Wood et al, 2020). However, the T6SS is not restricted to bacterial antagonism and can mediate host-pathogen interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Genes encoding for the Type VI Secretion System (T6SS) are present in more than 25% of Proteobacteria (Bingle et al, 2008;Barret et al, 2013). The injection of a panel of T6SS effectors into competing bacteria promotes the fitness of T6SS-positive strains in polymicrobial environments, including the gut ecosystem (Coulthurst, 2019;Wood et al, 2020). However, the T6SS is not restricted to bacterial antagonism and can mediate host-pathogen interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The T6SS is present in nearly 25% of gram-negative pathogens, including Pseudomonas aeruginosa ( Mougous et al., 2006 ), Vibrio cholerae ( Basler et al., 2012 ; Fast et al., 2018 ), Burkholderia mallei ( Schwarz et al., 2010 ), Salmonella enterica ( Wang et al., 2011 ), and Campylobacter jejuni ( C. jejuni ) ( Noreen et al., 2018 ; Lertpiriyapong et al., 2012 ; Sha et al., 2013 ). A functional T6SS facilitates bacterial predation ( Cianfanelli et al., 2016 ), host cell adherence, and invasion ( Lertpiriyapong et al., 2012 ), conferring a selective advantage to the predator over other prey bacteria within the same environmental niche ( Dörr and Blokesch, 2018 ; Wood et al., 2020 ). However, an important question is how molecular activities of T6SS at a cellular level translate into ecological outcomes at a population level.…”
Section: Introductionmentioning
confidence: 99%
“…T6SSs have recently been shown to contribute to the adaptation of strains to their niche, such as the intestinal microbiota. T6SS, thus, could be a major player for adaptation to different niches, each being colonized by different microbiota [ 39 ]. To that end, it is interesting to note that, based on strains isolated from different sources in Australia, Touchon et al showed strong associations between the phylogenetic structure of populations and the natural habitats of strains [ 32 ].…”
Section: Discussionmentioning
confidence: 99%